Vitamin D Supplementation and COVID-19 - Gracia Dewitacita Tanaya; Willa Mettacita Tanaya; Ayu Hutami Syarif (Jurnal Respirasi, 2022)
Coronavirus Disease 2019 (COVID-19) happened due to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. It is the third coronavirus causing a pandemic. Cases of COVID-19 have increased rapidly. Epidemiological studies show droplets as a medium of transmission of this virus. The high rate of transmission and the death rate create urgency on the management of COVID-19. Unfortunately, until now there is no definitive therapy for the SARS-CoV-2 virus. Several potential therapies, including antivirals, immunomodulatory agents, convalescent plasma transfusions, and supportive therapies such as vitamin D supplementation, have been applied in the management of COVID-19. As a hormone, vitamin D has an immunomodulatory effect used in supportive therapy for various immune-related diseases and respiratory system infections. The immunomodulatory effects of vitamin D are strengthening the physical barrier (cell junction), the specific immune system (adaptive immunity), and the non-specific immune system (innate immunity). Vitamin D is known to suppress pro-inflammatory cytokines and increase the production of anti-inflammatory cytokines. In addition, vitamin D also performs as a substantial part in the induction of ACE2 receptors which gives a weighty influence on pathogenesis of COVID-19. Vitamin D deficiency can amplify the risk of infections including COVID-19. Presently, clinical trials of vitamin D supplementation and COVID-19 are limited. This literature review further examined the role of vitamin D supplementation in COVID-19.